2016
DOI: 10.1007/s40265-016-0592-1
|View full text |Cite
|
Sign up to set email alerts
|

Fimasartan: A New Angiotensin Receptor Blocker

Abstract: Fimasartan is the ninth, and most recent, angiotensin II receptor antagonist approved as an antihypertensive agent. Fimasartan, a pyrimidin-4(3H)-one derivative of losartan with the imidazole ring replaced, which enables higher potency and longer duration than losartan. Fecal elimination and biliary excretion are the predominant elimination pathways of fimasartan and the urinary excretion was found to be less than 3 % 24 h after administration. Fimasartan is primarily catabolized by cytochrome P450 isoform 3A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Another challenge we faced is whether the findings in the present study were ARB class effects or fimasartan‐specific effects. Since its launch in 2011, use of 60 to 120 mg/day of fimasartan has shown excellent efficacy in BP reduction and an excellent safety profile in a large, population‐based observational study, and cardiovascular‐protective effects in various preclinical studies . A large‐scale prospective cohort study (K‐MetS study) is currently ongoing to evaluate whether the reduction in BP and/or correction of metabolic derangements with fimasartan will affect major adverse cardiovascular events and the development of diabetes after long‐term use in people with hypertension .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another challenge we faced is whether the findings in the present study were ARB class effects or fimasartan‐specific effects. Since its launch in 2011, use of 60 to 120 mg/day of fimasartan has shown excellent efficacy in BP reduction and an excellent safety profile in a large, population‐based observational study, and cardiovascular‐protective effects in various preclinical studies . A large‐scale prospective cohort study (K‐MetS study) is currently ongoing to evaluate whether the reduction in BP and/or correction of metabolic derangements with fimasartan will affect major adverse cardiovascular events and the development of diabetes after long‐term use in people with hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the effects of fimasartan on insulin secretion in patients with type 2 diabetes and hypertension. Fimasartan, a newly developed ARB approved as an antihypertensive agent, is a pyrimidin‐4(3H)‐one derivative of losartan with the imidazole ring replaced, which enables higher potency and longer duration of action of the angiotensin II type 1 receptor, compared with losartan …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fimasartan is the ninth and the most recent ARB to be approved by the Korean Food and Drug Association as an antihypertensive agent [7][8][9]. In previous studies, fimasartan was shown to exert protective effects in animal models of myocardial ischemia: the suppression of apoptosis [10] and the prevention of intimal thickening and plaque rupture [11].…”
Section: Introductionmentioning
confidence: 99%
“…6 It is the ninth and most recent ARB approved for use in HTN by the Korea Food and Drug Administration, and is also available for worldwide use. 7 Fimasartan has been shown to have non-inferior, or even superior blood pressurelowering capabilities compared with losartan, 8,9 and has also proven its safety in previous trials. 10,11 Unlike other ARBs, fimasartan is predominantly excreted through the hepatobiliary system, with less than 3% of the administered dose detected in the urine.…”
Section: Introductionmentioning
confidence: 99%